The theses for MD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Т.G. Zaviktorina - Clinical value of gastroesophageal and pharyngolaryngeal refluxes at esophagus and larynx diseases in pediatrics.Ye.B. Yaroshenko – Comparative clinical characteristic of liver cirrhosis of various etiology.O.G. Stepanov – Regulatory disorders in pathogenesis of irritable bowel syndrome in children.